INTERNATIONAL COMMODITY PRICE SHOCKS AND NIGERIAN HOUSEHOLDS, 2006 - 2011 (2014)
Nigeria’s dependence on food and refined oil importations makes households vulnerable to price shocks of these commodities. While there is a growing body of empirical literature on the consequence of international commodity price shocks, there is little attempt to investigate their effects on households. This study, therefore, examined the effects of international price shocks to food and refined oil on household income and consumption in Nigeria. A recursive-dynamic computable general equilibrium model, based on the Walrasian theory of market behaviour, was employed. The model was able to analyse the income and consumption effects of food and refined oil price shocks on households as it captured changes in the relative prices of product and factor goods. The model had production, income and savings, demand, international trade, prices, equilibrium, and dynamic blocks. It was calibrated using a modified 2006 Nigeria Social Accounting Matrix (SAM). In the SAM, households were categorised into rural poor (RP), rural non-poor (RNP), urban poor (UP) and urban non-poor (UNP). Capital stocks were considered using investment, while labour supply and the minimum consumption of households were adjusted each period by population growth rate in order to capture the dynamic adjustment path of households to food and refined oil price shocks over a five-year (2006 - 2011) horizon. Diagnostic tests (baseline simulation test and Leon) and sensitivity analyses were carried out to ascertain the model’s consistency as well as the robustness of the simulation outcomes. A 37.0% positive shock in the international food prices increased incomes of RP, RNP, UP and UNP households by 2.4%, 2.9%, 1.9% and 1.5%, respectively, as domestic supply response increased all categories of household labour income by 2.1%, and RP and UP households’ capital income by 3.5%. Consumption declined by 1.4%, 0.8% and 0.2% for RP, UP and UNP households, respectively, partly because the domestic prices of major products consumed by these households rose between 0.55% and 6.48%. However, as RNP household income increased by 2.9%, consumption rose by 0.61%. In contrast, a positive shock in the international price of refined oil by 60.0% reduced RP, RNP, UP and UNP households income by 6.1%, 5.5%, 5.6% and 4.3%, respectively, due to weak domestic supply response engendered by the small labour absorption (less than 0.1%) in the refined oil sector and low oil-refining capacity. Also, consumption of RP, RNP, UP and UNP households correspondingly declined by 2.5%, 2.6%, 2.7% and 2% owing to declines in household incomes and increase in the domestic prices of some commodities by 13.3%, on average. These results were partly due to the large share of imported refined oil and the relative substantial domestic production of food. Positive shocks to the international price of refined oil adversely affected households’ income and consumption in Nigeria between 2006 - 2011. Similar shocks to international food prices increased household income but adversely affected consumption. Increased domestic production of food and refined oil may reduce the negative effects of international price shocks to these commodities.